1993
DOI: 10.1159/000236498
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Containing Nerve Fibers in Human Airways: Distribution and Coexistence Pattern

Abstract: The occurrence, distribution and coexistence pattern of an array of neuropeptides and tyrosine hydroxylase in the human larynx, trachea, bronchi and lungs were studied by immunocytochemistry. A rich supply of nerve fibers containing vasoactive intestinal peptide (VIP) was seen close to blood vessels, glands and nonvascular smooth muscle. Pituitary adenylate cyclase-activating peptide (PACAP)-containing fibers were numerous among bundles of smooth muscle. Moderate numbers of helospectin-containing nerve fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…Substance P is present in nerve profiles, found beneath and within the epithelium and around submucosal glands. 41,42 Furthermore, Chu et al 43 demonstrated that epithelial cells are an additional source of substance P. They also demonstrated expression of the tachykinin NK 1 receptor on goblet cells. Further evidence for this hypothesis is provided by their work demonstrating increased expression of substance P and its receptor in asthmatics, which was correlated with the mucus content in the airway epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Substance P is present in nerve profiles, found beneath and within the epithelium and around submucosal glands. 41,42 Furthermore, Chu et al 43 demonstrated that epithelial cells are an additional source of substance P. They also demonstrated expression of the tachykinin NK 1 receptor on goblet cells. Further evidence for this hypothesis is provided by their work demonstrating increased expression of substance P and its receptor in asthmatics, which was correlated with the mucus content in the airway epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In the human airways, they are contained within sensory unmyelinated C nerve fibres, which are distributed beneath or within the airway epithelium, around blood vessels and glands, within the bronchial smooth muscle layer and around local ganglion cells [4][5][6][7][8]. Recent findings in both experimental animals and humans, however, suggest that non-neural cells (endothelial cells, eosinophils and macrophages), either resident or circulating, can also be a source of tachykinins and that immune stimuli can boost tachykinin production from immunocytes [9].…”
mentioning
confidence: 99%
“…Nerve fibres containing vasoactive intestinal polypeptide (VIP), calcitonin gene-related peptide (CGRP), substance P (SP) and neuropeptide Y (NPY) are seen around pulmonary blood vessels and close to small bronchioles [3]. Endocrine cells, solitary as well as clustered, can be seen in bronchi and bronchioles [4].…”
mentioning
confidence: 99%